Structure-mechanism-based engineering of chemical regulators targeting distinct pathological factors in Alzheimer’s disease - Beck, Michael W.; Derrick, Jeffrey S.; Kerr, Richard A.; Oh, Shin Bi; Cho, Woo Jong; Lee, Shin Jung C.; Ji, Yonghwan; Han, Jiyeon; Tehrani, Zahra Aliakbar; Suh, Nayoung; Kim, Sujeong; Larsen, Scott D.; et al. (Nature communications, 2016)
The absence of effective therapeutics against Alzheimer’s disease (AD) is a result of the limited understanding of its multifaceted aetiology. Because of the lack of chemical tools to identify pathological factors, investigations into AD pathogenesis have also been insubstantial. Here we report chemical regulators that demonstrate distinct specificity towards targets linked to AD pathology, including metals, amyloid-β (Aβ), metal–Aβ, reactive oxygen species, and free organic radicals. We obtained these chemical regulators through a rational structure-mechanism-based design strategy. We performed structural variations of small molecules for fine-tuning their electronic properties, such as ionization potentials and mechanistic pathways for reactivity towards different targets. We established in vitro and/or in vivo efficacies of the regulators for modulating their targets’ reactivities, ameliorating toxicity, reducing amyloid pathology, and improving cognitive deficits. Our chemical tools show promise for deciphering AD pathogenesis and discovering effective drugs. To advance our understanding of pathological features associated with Alzheimer’s disease (AD), chemical tools with distinct specificity towards AD targets would be valuable. Here the authors used a structure-mechanism-based design strategy to obtain small molecules as chemical regulators for distinct pathological factors linked to AD pathology.